OVERVIEW OF PHYTOCHEMICAL COMPOUNDS AND PHARMACOLOGICAL ACTIVITIES OF Borassus flabellifer Linn. AS A REGIONAL EMBLEM PLANT OF SOUTH SULAWESI - Agus, Wahyuni (JURNAL PHARMA BHAKTA, 2025)
Background: Borassus flabellifer Linn. (palmyra palm) is a member of the Arecaceae family with important ecological, economic, and pharmacological roles, and serves as the floral emblem of South Sulawesi, Indonesia. Traditionally, almost all parts of the plant have been used for food, beverages, and handicrafts. Objective: This review summarizes its phytochemical constituents and pharmacological activities. Methods: Relevant articles were collected from Scopus, ScienceDirect, PubMed, and Google Scholar. Publications from 2005 to 2025 were screened using the keywords Borassus flabellifer, palmyra palm, phytochemistry, and pharmacological activity. Based on inclusion and exclusion criteria, 19 articles were analyzed. Result: Findings indicate that plant parts contain bioactive compounds such as flavonoids, phenols, alkaloids, saponins, tannins, terpenoids, and steroidal saponins including flabelliferins and borassosides. These metabolites are linked to antioxidant, anti-inflammatory, cytotoxic, antidiabetic, antibacterial, antifungal, and diuretic effects, through mechanisms such as free radical scavenging, suppression of inflammation, induction of apoptosis, inhibition of carbohydrate-digesting enzymes, and regulation of renal electrolyte excretion. Conclusion: Overall, Borassus flabellifer shows strong potential as a source of phytopharmaceuticals and natural drug candidates. Beyond pharmacological value, its ecological resilience, cultural significance, and economic importance support its designation as the floral emblem of South Sulawesi. Further preclinical and clinical studies are needed to validate therapeutic efficacy and safety.